Surface Micro-Hardness and Wear Resistance of a Self-Adhesive Flowable Composite in Comparison to Conventional Flowable Composites - Fateme Azizi; Fariba Ezoji; Soraya Khafri; Behnaz Esmaeili (Tehran University of Medical Sciences, 2023)
Objectives: The durability of composite restorations is directly affected by the mechanical properties of the composite. The aim of this study was to evaluate the hardness and wear resistance of self-adhesive flowable composite (SAF) in comparison with conventional flowable composites. Materials and Methods: In this in vitro study, 50 composite specimens were prepared in brass molds with 10mm ×10mm ×2mm and divided into five groups (n=10). Specimens included three conventional flowable composites (Grandio flow, Filtek flow and Admira fusion flow), one self-adhering flowable composite (SAF, Vertise flow) and a microhybrid composite (filtek z250). After polishing, the micro-hardness of the specimens was measured in a Vickers hardness device, and the specimens were then subjected to 5000, 10000, 20000, 40000, 80000 and 120000 wear cycles in a wear tester. One-way ANOVA/Games-Howell, Kruskal Wallis, and Friedman tests were used for statistical analysis. The significance level was set at P<0.05. Results: The surface micro-hardness of the SAF was significantly lower than that of the microhybrid composite (P=0.01). There was no significant difference between the surface hardness of the different tested flowable composites (P>0.05). Also, the wear resistance of the studied composites was not significantly different in various cycles (P>0.05). Conclusion: Based on our results, SAF would not be an ideal substitute for conventional flowable composites in high-stress areas.